Memory footprint: Predictors of flashbulb and event memories of the 2016 Euro Cup final - Ribeiro, Andreia; Marques, Margarida; Roberto, Magda S.; Raposo, Ana (Frontiers in Psychology, 2023)
Two years after Portugal won the UEFA European Championship, we examined what the Portuguese remember of this momentous occasion. We investigated if flashbulb memories (FBMs) and event memories (EMs) were determined by distinct factors, and whether EM was a predictor of FBM. Participants responded to an online questionnaire about their FBM, EM and a set of predictors. The structural equation model proposed by Tinti et al. (2014) was adapted, to incorporate some improvements regarding the measurement procedure, and tested. Results revealed that FBM and EM were associated with different pathways. Interest in football predicted importance which triggered emotional intensity which predicted personal rehearsal, a direct determinant of FBMs. On the other pathway, interest determined knowledge about football, the main predictor of EMs. Importantly, EM was a causal determinant of FBM which shows that the memory trace for the original event enhances memory for the reception context. The findings suggests that even though the two types of memories are determined by independent factors, they interact very closely.